Investor Protections and Concentrated Ownership: Assessing Corporate Control Mechanisms in the Netherlands - Robert S. Chirinko; Hans van Ees; Harry Garretsen; Elmer Sterken (Center for Economic Studies and ifo Institute (CESifo), 2003)
The Berle-Means problem - information and incentive asymmetries disrupting relations between knowledgeable managers and remote investors - has remained a durable issue engaging researchers since the 1930's. However, the Berle-Means paradigm - widely-dispersed, helpless investors facing strong, entrenched managers - is under stress in the wake of the cross-country evidence presented by La Porta, Lopez-de-Silanes, Shleifer, and Vishny and their legal approach to corporate control. This paper continues to investigate the roles of investor protections and concentrated ownership by examining firm behaviour in the Netherlands. Our within country analysis generates two key results. First, the role of investor protections emphasized in the legal approach is not sustained. Rather, we find that performance is enhanced when the firm is freed of equity market constraints, a result that we attribute to the relaxation of the myopia constraints imposed by relatively uninformed investors. Second, ownership concentration does not have a discernible impact on firm performance, which may reflect large shareholders' dual role in lowering the costs of managerial agency problems but raising the agency costs of expropriation.
Keywords: G30; 330